Islamic perspective of women involvement in dispute resolution and maintaining peace at community level: case study in Malaysia and Pakistan / Hanna Ambaras Khan ... [et al.] - Khan, Hanna Ambaras; Mehmood, Muhammad Ifzal; Abdul Hak, Nora; Dastagir, Ghulam (Universiti Teknologi MARA, 2020)
Islam never exclude women in making contribution in dispute resolution and maintaining the harmony in the society. Women is play key-roles in the administration of social problems in every society if they are given opportunities and support by the authority. In many Islamic or Muslims majority countries, there are different tools used to resolve the dispute at the community level keeping up the peace in the society. In Pakistan, there is a parallel or informal judicial system for dispute resolution named Jirga or Panchayats. The members of Jirga or Panchayats are the influential people or elders of the community. Unfortunately, until today there is no female representation in both systems. Women are barred from consultation in disputes resolution at community level, which have created discrimination against woman. On the other hand, in Malaysia, the Department of National Unity and Integration has trained women to be community mediators in resolving neighborhood disputes at the community level. Islam encourages the Muslim to keep peace in the society without restricting involvement of women. This paper discusses the disputes resolution in Islam and women participation, roles of female involvement in resolving neighborhood disputes at community level in Malaysia and the system of Jirga and Panchayat in Pakistan. Subsequently, this paper makes some suggestion in including women participation in dispute resolution and maintaining peace in Pakistan.